Analysis of Land Use Change in Upper Serayu Watersheds Using Remote Sensing and Geographic Information Systems - Susanti, Yuari; Syafrudin, Syafrudin; Helmi, Muhammad (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2020)
Globalization and the development of science and technology cause human needs increase. This has an effect on land use, especially in watershed areas. Serayu is one of watershed in Central Java which is have problems related to land use, which occurs in the upper of the watershed. Agricultural Intensification, deforestation, an increase in population are factors that drives land use changes in the upper of Serayu watershed. The utilization of watershed areas that ignore spatial rules causes pollution and land degradation. That condition happened and this makes the Serayu watershed one of the priority watersheds for rehabilitation in Indonesia. Remote Sensing (RS) and Geographic Information Systems (GIS) are tools that used to analyze land use changes that occurred in 2009-2019. Land use are classified into six classes ; water bodies (rivers, lakes, ponds), built-up areas, shrubs, forests, agriculture (rice fields, fields), and empty land.